2017
DOI: 10.1053/j.gastro.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Hypoxia Inducible Factor 1α Subunit Pathway in Steatotic Liver Contributes to Formation of Cholesterol Gallstones

Abstract: In steatotic livers of mice, hypoxia up-regulates expression of HIF1A, which reduces expression of AQP8 and concentrates biliary lipids via suppression of water secretion from hepatocytes. This promotes cholesterol gallstone formation. Livers from patients with NAFLD and gallstones express higher levels of HIF1A than livers from patients with NAFLD without gallstones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 75 publications
1
39
1
Order By: Relevance
“…Premetastatic liver cells of melanoma B16‐bearing mice exhibited the opposite pattern, as they displayed more intensive VEGFA immunostaining of endothelial cells localized in the large median hepatic lobe. The levels of VEGFA are known to be increased under hypoxic conditions, which explains the more prominent VEGFA expression in the periphery of the normal liver. In the premetastatic liver, the VEGFA expression was increased in the central parts of the organ, which was consistent with reported data on the upregulation of VEGFA in synchronous liver metastasis‐adjacent tissue compared with metastatic tissue per se in colorectal carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…Premetastatic liver cells of melanoma B16‐bearing mice exhibited the opposite pattern, as they displayed more intensive VEGFA immunostaining of endothelial cells localized in the large median hepatic lobe. The levels of VEGFA are known to be increased under hypoxic conditions, which explains the more prominent VEGFA expression in the periphery of the normal liver. In the premetastatic liver, the VEGFA expression was increased in the central parts of the organ, which was consistent with reported data on the upregulation of VEGFA in synchronous liver metastasis‐adjacent tissue compared with metastatic tissue per se in colorectal carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…Relative changes in gene expressions were determined using the 2 -ΔΔCt method. ΔCt refers to the cycle number at which the transcripts were detectable (Ct) normalized to the cycle number of CDKN1B [ 27 ]…”
Section: Methodsmentioning
confidence: 99%
“…Asai et al . [60 ▪▪ ] found that expression of aquaporin-8 (AQP8), a water channel that is responsible for hepatic water secretion into the bile canaliculi [6163], is markedly increased in the inducible hepatocyte-selective HIF1A knockout mice fed the lithogenic diet for 2 weeks. These changes dramatically increase bile flow by 35%, dilute biliary lipid concentrations by 36% in both gallbladder and hepatic bile, and alleviate gallbladder inflammation.…”
Section: The Latest Advances In the Pathophysiology Of Gallstones Fromentioning
confidence: 99%